(untitled) (Perner’s Contacts, 2016)
The article deals with the possibilities of change of adhesion conditions between vehicle wheels and the surface of the road. Article presents currently known ways how contact conditions between car wheels and the surface of the road can be influenced. At the same time the pros and cons of each solution are presented and also the proposal of a new type of adhesive control conditions in the form of SlideWheel.